Classycal Electrodynamics - Jackson, John David (John Wiley & Sons, Inc, 1999)
Introduction to electrostatics -- Boundary-Value problems in electrostatics: I -- Boundary-Value problems in electrostatics: II -- Multipoles, electrostatics of macroscopic media, dielectrics -- Magnetostatics, Fraday's law, quasi-static fields -- Maxwell equations, macroscopic electromagetism, conservation laws -- Plane electromagnetic waves and wave propagation -- Waveguides, resonant cavities, and optical fibers -- Radiating systems, multipole fields and radiation -- Scattering and diffraction -- Special theory of relativity -- Dynamics of relativistic particles and electromagnetic fields -- Collisions, energy loss, and scattering of charged particles, cherenkov and transition radiation -- Radiation by moving charges -- Bremsstrahlung, method of virtual quanta, radiative beta processes -- Radiation damping, classical models.